A guide to clinical research supervision for psychiatrists: a mentoring approach. (February 2015) - Looi, Jeffrey C; Kisely, Steve; Macfarlane, Matthew D; Siskind, Dan; Smith, Geoff; Macfarlane, Stephen
Objectives: To provide a guide for clinically-based psychiatrist supervisors of research projects for early career researchers. Methods: This paper will describe a mentoring framework for supervision, for psychiatrist clinical research supervisors and early career researchers. Results: The domains discussed include, across various aspects of a study: the role of the supervisor, project management, and where and when to seek advice. Conclusions: Supervision of clinical research can be a professionally rewarding experience for psychiatrists, as well as early career researcher supervisees.